Tingkah Laku Pemijahan Oryzias woworae Ikan Padi Endemik Pulau Muna, Sulawesi Tenggara Berdasarkan Nisbah Kelamin Induk Berbeda - Mohamad Ayip Firmansyah; Mustahal Mustahal; Mas Bayu Syamsunarno; Ilham Septian; Muh. Herjayanto (Fakultas Perikanan dan Ilmu Kelautan, Universitas Papua, 2022)
Ricefish Oryzias woworae is a species of ricefish endemic in the waters of Muna Island, Southeast Sulawesi. The economic potential of O. woworae as an ornamental fish has not been supported by the availability of information on its cultivation. One important aspect of the success of fish farming is knowledge of its reproduction. Spawning behavior information is very important to know. This study aims to examine the spawning behavior of rice fish O. woworae and the number of eggs per hour with different sex ratios of the broodstock. The research method uses an experimental design of parent sex ratio treatment female (♀) and male (♂) fish, namely 1♂ : 2♀ , 1♂ : 3♀, and 1♂ : 4♀. Prior to the study, the broodstock were acclimatized for seven days by feeding Artemia polar red. Observation of spawning behavior was carried out for five days. Observations were made every hour on the day of spawning. The results showed that O. woworae only spawned during the day between 06:00 and 16:00, with dominant synchronization behavior occurring in the morning which began to occur simultaneously on the third spawning day. Management that can be done regarding the phenomenon of brood fish-eating eggs is to put more spawning substrates for use by broodstock broodfish O. woworae to hide the eggs, so they are not eaten by other females during mass spawning. Another management method is to harvest eggs at the day and afternoon.